Plasminogen Activator (Urokinase) from Cultured Cells - Lewis, L James (Thrombosis and Haemostasis, 1979)
Secretion of large quantities of urokinase by cultured renal cells suggested tissue culture as a means of production to meet demand for the material and to obtain guidelines for optimization of production. Rates of secretion and overall yields of urokinase from confluent cultures of renal cells have been studied in relation to species differences, effects of passage of cells, inoculum density, and volume of maintenance media. Aided in part by an advantage gained through addition of glycine to maintenance media, it is now possible to harvest urokinase at concentrations of the order of 800 CTA units per ml. Such concentrations are of the order of 102 times that occurring in human male urine.